Etiology and the challenge of diagnostic testing of community-acquired pneumonia in children and adolescents (2022)
ABSTRACT: Background: Pneumonia is the leading cause of mortality in pediatric population. The etiology of pneumonia in this population is variable and changes according to age and disease severity and where the study is conducted. Our aim was to determine the etiology of community-acquired pneumonia (CAP) in children aged 1 month to 17 years admitted to 13 Colombian hospitals. Methods: Prospective cohort study. Hospitalized children with radiologically confirmed CAP and ≤ 15 days of symptoms were included and followed together with a control group. Induced sputum (IS) was submitted for stains and cultures for pyogenic bacteria and Mycobacterium tuberculosis, and multiplex PCR (mPCR) for bacteria and viruses; urinary antigens for pneumococcus and Legionella pneumophila; nasopharyngeal swabs for viruses, and paired serology for atypical bacteria and viruses. Additional cultures were taken at the discretion of primary care pediatricians. Results: Among 525 children with CAP, 71.6% had non-severe pneumonia; 24.8% severe and 3.6% very severe pneumonia, and no fatal cases. At least one microorganism was identified in 84% of children and 61% were of mixed etiology; 72% had at least one respiratory virus, 28% pyogenic bacteria and 21% atypical bacteria. Respiratory syncytial virus, Parainfluenza, Rhinovirus, Influenza, Mycoplasma pneumoniae, Adenovirus and Streptococcus pneumoniae were the most common etiologies of CAP. Respiratory syncytial virus was more frequent in children under 2 years and in severe pneumonia. Tuberculosis was diagnosed in 2.3% of children. IS was the most useful specimen to identify the etiology (33.6%), and blood cultures were positive in 3.6%. The concordance between all available diagnostic tests was low. A high percentage of healthy children were colonized by S. pneumoniae and Haemophilus influenzae, or were infected by Parainfluenza, Rhinovirus, Influenza and Adenovirus. Conclusions: Respiratory viruses are the most frequent etiology of CAP in children and adolescents, in particular in those under 5 years. This study shows the challenges in making an etiologic diagnosis of CAP in pediatric population because of the poor concordance between tests and the high percentage of multiple microorganisms in healthy children. IS is useful for CAP diagnosis in pediatric population. Keywords: Children; Diagnosis; Etiology; Induced sputum; Multiplex PCR; Nasopharyngeal swab; Pneumonia; Serology; Urine antigen.